ChemInform Abstract: Clerodendrumol, a New Triterpenoid from Clerodendrum yaundense Guerke (Lamiaceae). Issue 28 (June 2016) - Awouafack, Maurice D.; Aimaiti, Simayijiang; Tane, Pierre; Morita, Hiroyuki
Abstract: New triterpenoid, clerodendrumol (Ia) is isolated together with five known compounds.